Visual quality analysis using the Chinese Catquest-9SF scale following different spherical aberration IOL implantation - Wei, Du; Wei, Lou; Yanjun, Hua; Zequan, Xu; Lei, Jin; Qiang, Wu (Frontiers in Public Health, 2022)
Purpose: Based on the Chinese version of the Catquest-9SF scale, the contrast sensitivity meter and wavefront aberrometer were used to evaluate the visual quality of cataract patients implanted with different spherical aberrations IOL. Design: Retrospective Observational Study Methods: Patients who have the lens implantation in our department from January 2020 to December 2021 were enrolled. all patients underwent uncorrected visual acuity, best corrected visual acuity and slit lamp microscope, high-order aberrations and contrast sensitivity test.The KR-1W wavefront analyzer (Topcon Medical System, Tokyo, Japan) was used to measure wavefront aberrations post-operation. The Chinese Catquest-9SF scale was used to score the postoperative visual satisfaction of the patients. Results: 145 patients were screened according to the exclusion criteria, including 51 patients in the zero aspherical IOL(SOFTEC HD)group and 42 patients in the negative aspherical IOL(ZCB00)group ,a total of 52 cases in spherical IOL( HQ-201HEP)group. The score was highest in the zero spherical aberration group, followed by the negative spherical aberration group with lowest scores in the spherical IOL group. Higher-order aberrations are relatively low in eyes implanted with the zero spherical aberration group. Contrast sensitivity with spherical lenses under glare-free and glare conditions was lower than with aspheric lenses, and at higher frequencies the zero-aberration aspheric lens performed best. Conclusions: The Chinese Catquest-9SF scale provides an indication of visual quality after aspheric IOL implantation.